Cutaneous Plasmacytosis with Perineural Involvement. (6th February 2014) - Brezinski, Elizabeth A.; Fung, Maxwell A.; Fazel, Nasim
Abstract : Importance . Cutaneous and systemic plasmacytosis are rare conditions of unknown etiology with characteristic red-brown skin lesions and a mature polyclonal plasma cell infiltrate within the dermis. Perineural plasma cell infiltrates may be a histologic clue to the diagnosis of cutaneous plasmacytosis. Observations . Our patient had a five-year history of persistent reddish-brown plaques on the neck and trunk without systemic symptoms. Histologic examination showed dermal perivascular and perineural plasma cells with excess lambda light chain expression. Due to decreased quality of life caused by his skin lesions, he was placed on a chemotherapeutic regimen with bortezomib. Conclusions and Relevance . The patient was diagnosed with cutaneous plasmacytosis based on classic histopathology results with a recently characterized pattern of perineural involvement. Bortezomib therapy was initiated to manage his skin eruption, which has not been previously described as a treatment for this chronic condition.